2019
DOI: 10.1063/1.5080942
|View full text |Cite
|
Sign up to set email alerts
|

The role of hydrophobicity in the cold denaturation of proteins under high pressure: A study on apomyoglobin

Abstract: An exciting debate arises when microscopic mechanisms involved in the denaturation of proteins at high pressures are explained. In particular, the issue emerges when the hydrophobic effect is invoked, given that hydrophobicity cannot elucidate by itself the volume changes measured during protein unfolding. In this work, we study by the use of molecular dynamics simulations and essential dynamics analysis the relation between the solvation dynamics, volume, and water structure when apomyoglobin is subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
(83 reference statements)
1
1
0
Order By: Relevance
“…The cold denaturation may be due to temperature-dependent hydration of hydrophobic residues that becomes more thermodynamically favourable as temperature decreases. [57][58][59] Overall, the present study has not only demonstrated that canonical Ca 2+ binding to human LETM1 EF1 leads to increased hydrophobic exposure and oligomerization but also exposed several unique properties for this EFhand motif. Specifically, we have discovered that Ca 2+ binding, pH and temperature are robustly coupled with folding of the motif at physiologically relevant temperature and pH ranges.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The cold denaturation may be due to temperature-dependent hydration of hydrophobic residues that becomes more thermodynamically favourable as temperature decreases. [57][58][59] Overall, the present study has not only demonstrated that canonical Ca 2+ binding to human LETM1 EF1 leads to increased hydrophobic exposure and oligomerization but also exposed several unique properties for this EFhand motif. Specifically, we have discovered that Ca 2+ binding, pH and temperature are robustly coupled with folding of the motif at physiologically relevant temperature and pH ranges.…”
Section: Discussionsupporting
confidence: 53%
“…Consistently, decreasing the temperature to 4°C also decreased the Ca 2+ binding affinity ~4‐fold (Figure 3; Table 2). The cold denaturation may be due to temperature‐dependent hydration of hydrophobic residues that becomes more thermodynamically favourable as temperature decreases 57–59 …”
Section: Discussionmentioning
confidence: 99%